"Iavazzo score", a preoperative score to predict duration of robotic‐assisted gynaecological surgeries. Issue 4 (10th April 2022) - Iavazzo, Christos; Fotiou, Alexandros; Kokkali, Kalliopi; Vorgias, George
Abstract: Background: Long operation time remains a disadvantage of robotic‐assisted gynaecological procedures. A score that predicts the duration of such surgeries could be useful. Methods: A retrospective analysis of robotic‐assisted gynaecological surgeries in our institution were conducted. We assessed preoperative values such as body mass index, uterine size, previous abdominal surgeries, way of previous deliveries and pathology that led patients to the theatre and we created a preoperative predictive score, the 'Iavazzo score'. Thereafter, we correlated this score with duration of surgery. Results: 57 patients were included. Mean 'Iavazzo' score was 7.96, while mean surgery and overall time were 140 and 208.8 min, respectively. Correlation between Iavazzo score and operation time was statistically significant ( p < 0.001). Using median operation time, we found an area under curve of 0.86 and a cut‐off value of 7.5 for Iavazzo score. Conclusions: 'Iavazzo' score can be a useful predictive score that evaluates duration of robotic‐assisted gynaecological surgeries.